MEMAKSIMALKAN POTENSI SETIAP SISWA DENGAN PEMBELAJARAN BERDIFERENSIASI - Dwi Retno Sriwahyuni; Dini Rakhmawati; Arri Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Implementation of the Merdeka Curriculum, schools are given greater autonomy to develop learning programs according to student characteristics and needs. Differentiated learning is very relevant to meet the needs of each diverse student. However, before differentiated learning is carried out, the first step is to conduct a diagnostic assessment. Diagnostic assessment aims to identify learners' deficiencies, strengths, knowledge, skills and characteristics over a period of time. Diagnostic assessment includes cognitive aspects and non-cognitive aspects. Cognitive assessment includes students' understanding of the material, while non-cognitive assessment includes students' interests, learning profiles, and learning styles. Based on the results of the diagnostic assessment, students' learning styles are divided into 3, namely visual learning styles, audiotory learning styles, and kinesthetic learning styles. By knowing the learning style of each student, the teacher can also design learning according to student characteristics, the teacher can maximize the potential of each student in learning activities. The diagnostic assessment analysis is used as a reference to develop a differentiated learning strategy, which is divided into four parts, namely; content, process, product and learning environment, where these four components influence each other. From the four differentiated learning strategies, teachers can compile a mapping of learning activities based on the four differentiated learning strategies based on the characteristics and needs of different students both learning styles and cognitive abilities of each student. Keywords: Diagnostic assessment, . Student learning styles, Differentiated learning.